Mulheres Rurais e Atividades não Agrícolas no Âmbito da Agricultura Familiar - Rosani Marisa Spanevello (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The theme of the study are the interconnections between family farming, rural women and non-agricultural activities. The objective was to analyze the inclusion of rural women in non-agricultural activities in scope of the family agriculture of the municipality of Arvorezinha, state of Rio Grande do Sul, Brazil. Of qualitative nature and delineated as a case study, the study involved the application of forms with 17 rural women enrolled in non-agricultural activities. Faced with a context of devaluation of female labor in traditional agricultural activities, the insertion in non-agricultural activities shows itself as an alternative economic source, at least partially affecting the financial independence of rural women, in addition to resulting in socio-cultural improvements, enhancing their social life and their quality of life. In this way, non-agricultural activities within the family agriculture are favorable to the empowerment of rural women, considering their monetary and non-monetary advantages. In this sense, it is necessary to study the potential of these activities in expanding the possibilities for women to stay in rural areas, taking into consideration that they are the main migrants to urban centers, due to the devaluation of their work as farmers.